Extrudable UHMWPE-based composites: prospects of application in additive technologies; Nanoscience and Technology: An International Journal; Vol. 8, iss. 2 - Panin S. V. Sergey Viktorovich; Kornienko L. A. Lyudmila Aleksandrovna; Aleksenko V. O. Vladislav Olegovich; Ivanova L. R. Larisa Ryurikovna; Shilko S. V. Sergey Viktorovich; Pleskachevsky Yu. M. Yury Mikhaylovich (2017, 2017)
Title screen